Effects of COVID-19 Pandemic and Post-Vaccination Period on Gastroenterology Practice in Turkey - Gök Sargın, Zeynep; Düşünceli, İbrahimhalil; Çelik, Ümüt (Turkish Journal of Gastroenterology, 2022)
Background: The sudden and intense burden due to the novel coronavirus (coronavirus disease 2019) pandemic has changed the priority of many health services. The highly contagious new variants and vaccination services have greatly impacted the daily practice of gastroenterologists. In the present study, we tried to evaluate the change in the daily practice of Turkish gastroenterologists in the coronavirus disease 2019 pandemic and the post-vaccination periods.Methods: A questionnaire was prepared using Google forms and sent online to 214 gastroenterologists registered with the Turkish Gastroenterology Association.Results: Approximately half of the gastroenterologists moved their endoscopy unit or gastroenterology clinic to another location in the hospital during the pandemic and about one-third of the endoscopy units were completely closed. About 56% of the respondents reported the interruption of endoscopic procedures and inpatient services. In total, 85% of gastroenterologists thought that follow-up and treatment of chronic patients were disrupted due to patients obtaining their medicine directly from pharmacies. After the first case in Turkey, 74% of gastroenterologists worked in coronavirus disease 2019 patient care services, 28% of gastroenterologists were infected with coronavirus disease 2019, and 3% believed they had a cross-infected patient(s). A total of 78% of gastroenterologists reported that patient management became difficult due to the change in the priority of other departments, and 60% of gastroenterologists confirmed that they experienced a decrease in income. In the post-vaccination period, 70% of gastroenterologists returned to their pre-pandemic working schedule and 31% noticed an increase in endoscopic cancer detection.Conclusion: Prolongation of the pandemic has seriously damaged the practice of gastroenterology and multidisciplinary patient management.Cite this article as: Gök Sargın Z, Düşünceli İ, Çelik Ü. Effects of COVID-19 pandemic and post-vaccination period on gastroenterology practice in Turkey. Turk J Gastroenterol. 2023; 34(1): 13-18.